2014
DOI: 10.1177/1535370214529387
|View full text |Cite
|
Sign up to set email alerts
|

Microphysiological modeling of the reproductive tract: A fertile endeavor

Abstract: Preclinical toxicity testing in animal models is a cornerstone of the drug development process, yet it is often unable to predict adverse effects and tolerability issues in human subjects. Species-specific responses to investigational drugs has led researchers to utilize human tissues and cells to better estimate human toxicity. Unfortunately, human cell-derived models are imperfect because toxicity is assessed in isolation, removed from the normal physiologic microenvironment. Microphysiological modeling, oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 120 publications
(216 reference statements)
0
33
0
Order By: Relevance
“…As noted above (section 3.3), these in vitro studies revealed that this toxicant acts to disrupt the anti-inflammatory action of progesterone, leading to an increase in endometrial cell sensitivity to inflammatory stimuli [17]. Nevertheless, mechanistic interpretation of these results remains limited as a consequence of a non-physiological experimental setting [144146]. Multi-cell culture assays, including organ cultures, co-cultures and tissue recombinants, clearly demonstrate the significant role of cell-cell communication in normal endometrial physiology [16, 147, 148].…”
Section: Developing a New Human Model For Reproductive Toxicologymentioning
confidence: 99%
“…As noted above (section 3.3), these in vitro studies revealed that this toxicant acts to disrupt the anti-inflammatory action of progesterone, leading to an increase in endometrial cell sensitivity to inflammatory stimuli [17]. Nevertheless, mechanistic interpretation of these results remains limited as a consequence of a non-physiological experimental setting [144146]. Multi-cell culture assays, including organ cultures, co-cultures and tissue recombinants, clearly demonstrate the significant role of cell-cell communication in normal endometrial physiology [16, 147, 148].…”
Section: Developing a New Human Model For Reproductive Toxicologymentioning
confidence: 99%
“…39 Next is a perspective on the scientific, practical, and governmental regulatory expectations for such efforts. 40 The body of the issue comprises fourteen articles describing constructs that can serve as in vitro models for bone and cartilage, 41 brain, 42 gastrointestinal tract, 43;44 lung, 45 liver, 46;47 microvasculature, 48 reproductive tract, 49 skeletal muscle, 50 and skin, 51 as well as the interconnection of organs-on-chips to support physiologically based pharmacokinetics 52 and anticancer drug screening. 53 These research areas will eventually benefit from microscale technologies that regulate stem cell differentiation.…”
Section: Why Are Microphysiological Systems Of Interest?mentioning
confidence: 99%
“…The recapitulation of the 28-day menstrual cycle and pregnant-like hormone control has been achieved through integrating multiple tissues into an MPS microfluidic culture system called EVATAR TM . 22 A microfluidic organ-on-chip model of the uterine endometrium (EndoChip) has been engineered to reassemble the endometrium (immune, vascular, stromal and epithelial components) to individually compartmentalize each cell type with control over endocrine and biomechanical stimuli (e.g. shear stresses).…”
Section: Gender-based Testingmentioning
confidence: 99%
“…Microphysiological modeling of hormonal balance has been presented in concept for the male reproductive tract. 22 Although there are no MPS data yet available on this challenge in a human MPS model, a three-dimensional co-culture model of rat testis development has shown promise for incorporating local metabolic capability and pharmacokinetics for phthalate male reproductive toxicants. 24 When anchored to developmental regulation of the testicular transcriptome the changes will capture critical processes in puberty such as the peak in steroidogenesis and increase in meiosis and spermatogenesis-related pathways during the first wave of spermatogenesis.…”
Section: Gender-based Testingmentioning
confidence: 99%